Reestruturações em três grandes grupos brasileiros: Villares, Gradiente e Abril - Barth, Stephan (1995)
The development of Villares, Gradiente and Abril - three large brazilian groups, is reviewed in a historical perspective. Theoretical aspects of reengineering, interpretive and funcionalist paradigms and other subjects related to effectiveness and eficacy of organizations are explored in the first three chapters. The following three, outline the major reestruturing processes of the groups, emphasizing the restructurations of the present decade. The final chapter analyses the main aspects of the processes contrasting the historical development of the companies with the reviewed literature to confirm the recent administrative maturity of the brazilian groups. A brief conclusion is provided considering the working hypotheses of the research.